Pengaruh Ukuran Dewan Direksi dan Islamic Corporate Social Responsibility terhadap Nilai Perusahaan: Studi pada Bank Syariah yang Terdaftar di OJK Tahun 2016-2020 - Ramadhani, Wulandary; Serly, Vanica (Jurnal Nuansa Karya Akuntansi, 2023)
The purpose of this study was to determine the effect of board size and Islamic corporate governance on firm value. The population in this study are Islamic Commercial Banks registered with the OJK. The research design in this study is a quantitative approach using secondary data. Secondary data is obtained from each website of Islamic Commercial Banks. We then analyzed the data using multiple linear regression analysis techniques. This research is (1) board size has a significant effect on firm value (2) Islamic corporate social responsibility has no effect on firm value.